Financing constraints and firms' cash policy in the euro area - Rozália Pál; Annalisa Ferrando (European Central Bank (ECB), 2006)
This paper investigates the financing conditions of non-financial corporations in the euro area. We develop a new firm classification based on micro data by distinguishing between three groups of firms: unconstrained, relatively and absolutely constrained firms. We also provide further evidence on the sources of the correlation between corporate cash flow and cash savings by conducting the analysis in a dynamic framework. Contrary to previous evidence based mainly on US firms, our results suggest that the propensity to save cash out of cash flows is significantly positive regardless of firms' financing conditions. This implies that even for firms with favourable external financing conditions, the internal cash flow is used in a systematic pattern for the inter-temporal allocation of capital. The results also indicate that the cash flow sensitivity of cash holdings cannot be used for testing financing constraints of euro area firms.
Keywords: D92; G3; G32; 330; cash policy decisions; financing conditions; Unternehmensfinanzierung; Cash Flow; Eurozone; EU-Staaten